Analysis of Green Banking Implementation, Capital Adequacy, and Company Size on the Profitability of Commercial Banks in Indonesia for the Period 2018 – 2023 - Dewi, Melliana; Nusantara, Agung (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the effect of green banking, capital adequacy, and company size on profitability in public banking in Indonesia for the period 2018- 2023. The data source of this research is secondary data obtained from annual reports and sustainability reports from each conventional public banking official website. Sample selection using purposive sampling method. Hypothesis testing using panel data regression method with Eviews 10 program. The results showed that capital adequacy and company size had a positive and significant effect on profitability. While green banking has no effect and is not significant to profitability. The results of this study can be used as practical banking implications to optimize capital adequacy and total assets in an effort to increase banking profitability.